Mechanochemical large-scale rapid synthesis of ultrapure sodium hexafluorophosphate - Senthilkumaran, Marimuthu; Javaregowda, Bharathkumar H.; Rajendran, Prakash Babu; Balasubramanian, Rajalakshmi; Ajithkumar, Thalasseril G.; Ravindranathan, Sapna; Krishnamoorthy, Kothandam (ChemPlusChem, 2025)
Among the sodium battery electrolytes, sodium hexafluorophosphate (NaPF6) exhibits superior conductivity, anodic stability, and stable cathode electrolyte interface compared to other electrolytes. Therefore, the synthesis of pure NaPF6 through a simple process is very important. Usually, NaPF6 is synthesized using HF. In our approach, NaPF6 is synthesized by grinding dry ammonium hexafluorophosphate (NH4PF6) and sodium metal. Sodium injects an electron into the ammonium ion, which results in the formation of ammonia and hydrogen. The gram scale synthesis is completed in about 30 min. Purification of the product is not needed. The product purity is confirmed by various spectroscopic and electrochemical techniques. Usually, NaPF6 comprises NaF, HF, and solvents as impurities that affect the performance of SIBs. It has been confirmed that the NaPF6 synthesized by our mechanochemical approach in the absence of solvent is devoid of impurities despite the absence of product purification step. Furthermore, the synthesis of pure NaPF6 (250 g) is demonstrated using a grinder used as household item in cooking Indian pancakes, which costs about 300 USD. The duration of the synthesis of 250 g pure NaPF6 is 1 h. The purity of this sample is comparable to that of NaPF6 (5 g) synthesized using mortar and pestle.
Keywords: ammonium hexafluorophosphate; Batteries; carbonates; sodium hexafluorophosphate; sodium vanadium phosphate

Insights into the structure and electrochemical properties of Ti3C2T x MXene from solid-state NMR - Balasubramanian, Rajalakshmi; Puthiyaveetil, Priyanka Pandinhare; Kurungot, Sreekumar; Ajithkumar, T. G. (Journal of Physical Chemistry C, 2026)
Ever since their discovery in 2011, MXenes have gained popularity in energy storage devices. Their far-reaching properties arise mainly due to surface terminations and interlayer species like hydrated cations and water. The nature of these species remains a subject of study due to the complex surface functionalization during synthesis. X-ray diffraction studies have shown that certain intercalants such as hydrated cations increase the interlayer spacing leading to enhanced electrochemical performance. However, the structural and chemical modification of these intercalants during the charge-discharge cycles of asymmetric supercapacitors are yet to be investigated. Analysis of the complex chemistry of Ti3C2Tx requires a specialized tool that can provide insights into its nuanced structural changes and link them to its behavior. In this study, we demonstrate the versatility of solid-state NMR (SSNMR), for the characterization of surface terminations and intercalants in the Ti3C2Tx MXene prepared using sodium salts, and correlate its structure to its performance by ex situ SSNMR analysis. Our experiments demonstrate the progressive oxidation of surface Ti-OH and also the significance of the intercalated hydrated cation shells during electrochemical cycling. In addition to this, we have also employed Na-23 MAS SSNMR to demonstrate the conversion of sodium hexahydrate to sodium peroxides after 10 charge-discharge cycles.

Self-healing hydrogel electrolyte enabled by dynamic polar covalent and noncovalent interactions for high-performance rechargeable zinc-metal batteries: a leap toward sustainable energy storage - Puthiyaveetil, Priyanka Pandinhare; Kurian, Rachna Maria; Samudre, Nikhil S.; Balasubramanian, Rajalakshmi; Torris, Arun; Pockil, Fayis Kanheeram; Bhat, Suresh; Ajithkumar, T. G.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Advanced Energy Materials, 2026)
Hydrogel polymer electrolytes with superior multifunctional properties are promising alternatives to aqueous electrolytes for resolving interfacial issues in rechargeable zinc-metal batteries. In this study, an intrinsic self-healing hydrogel polymer electrolyte (PHBC-4) is synthesized, engineered through an integrated approach involving the polar covalent (B & horbar;O bond), hydrogen-bond (polyvinyl alcohol-hydroxypropyl methylcellulose interface), and coordination-type (Zn & horbar;O) interactions to enable self-healing functionality. The PHBC-4 has demonstrated high ionic conductivity (4.6 x 10-2 S cm-1), good oxidative stability (2.3 V vs Zn|Zn2+), a high cation transference number (0.89), superior tensile strength (0.32 MPa), and an impressive healing efficiency of 93% achieved just within 5 min, confirming its robust self-healing capability. In Zn||Zn symmetric cells, it effectively suppresses dendrite growth, ensuring stable cycling for over 1032 h with an areal capacity of 1.0 mAh cm-2 at a current density of 1.0 mA cm-2. When paired with a Zn-doped MnO cathode in the rechargeable homemade pouch cell, the system delivers a high specific capacity of 160 mAh g-1 at 0.10 A g-1 and cycling stability up to 493 charge-discharge cycles at 2.0 A g-1. The self-healing ability of PHBC-4 HGPE is confirmed in a homemade pouch cell via OCV and charge-discharge tests, demonstrating stable performance. The DFT studies confirm molecular-level interactions within the hydrogel heterostructure.
Keywords: dendrite inhibition; flexible rechargeable zinc metal battery; high cation transference number; self-healing hydrogel polymer electrolyte